Respuesta :
13 -6x= (2x-5)^2+ 3
⇒ 13 -6x= 4x^2 -20x+ 25+ 3
⇒ 4x^2 -20x+ (25+3)= 13 -6x
⇒ 4x^2 -20x +6x+ 28 -13= 0
⇒ 4x^2+ (-20x+ 6x)+ (28-13)= 0 (combine like terms)
⇒ 4x^2 -14x+ 15= 0
The correct answer is b. 4x^2 -14x+ 15= 0~
⇒ 13 -6x= 4x^2 -20x+ 25+ 3
⇒ 4x^2 -20x+ (25+3)= 13 -6x
⇒ 4x^2 -20x +6x+ 28 -13= 0
⇒ 4x^2+ (-20x+ 6x)+ (28-13)= 0 (combine like terms)
⇒ 4x^2 -14x+ 15= 0
The correct answer is b. 4x^2 -14x+ 15= 0~
Answer: The correct option is (b) [tex]4x^2-14x+15=0.[/tex]
Step-by-step explanation: The given equation is
[tex]13-6x=(2x-5)^2+3.~~~~~~~~~~~~~(i)[/tex]
We are given to select the correct standard form of the above equation.
We will be using the following formula:
[tex](a-b)^2=a^2-2ab+b^2.[/tex]
From equation (i), we have
[tex]13-6x=(2x-5)^2+3\\\\\Rightarrow 13-6x=4x^2-20x+25+3\\\\\Rightarrow 13-6x=4x^2-20x+28\\\\\Rightarrow 4x^2-20x+28-13+6x=0\\\\\Rightarrow 4x^2-14x+15=0.[/tex]
Therefore, the correct standard form is [tex]4x^2-14x+15=0.[/tex]
Thus, (b) is the correct option.